SPANISH MULTICENTRIC STUDY ABOUT NUTRITION-INFLAMATIONhn WITH MID DILUTION (ENIMID STUDY): PRELIMINARY RESULTS - Barril G; Anaya S; Vozmediano C; Celayeta AO; Novillo R; Garcia-Bernal V; Beired I; Huarte E; JC Chacón; Martín J; Santana H; Grande J; et al. (The Korean Society of Nephrology, 2012)
The prevalence of malnutrition are 23-76% of ESRD patients undergoing HD, and 20-50% of them suffers inflammation. Nowadays, the "malnutrition-inflammation" duo is frequently found in HD patients.The aim of this Spanish multicenter study is to evaluate the effects of the Mid-Dilution HDF on the inflammatory-nutritional state, on some body composition and on the quality of life in the HD patients. The total number of patients expected 64; the preliminary analysis of 52 patient/3 months and 23 after 6months (the study will last 1 year), is presented. Methods: Patients undergoing standard HD treatment with High Flux dialyzers for 4 hours/three times a week passed to HDF Online MidDilution with OLPUR 220 filters at a reinfusion rate of 12l/h.The patients are classified by: age, gender, Charlson comorbidity index, dialysis vintage. The parameters analyzed each 3 months are: urea, β2microglobuline, albumin, pre-albumin, CRP, fibrinogen, IL6, IL10, leptin, adiponectin, neuropeptide Y, body composition by BIVA parameters and apetite and quality life surveys. RESULTS: Patients classification: • Age: 64.06±0.8 years; • Sex: 64% male; • Charlson-index: 3.97±1.66; • HD vintage 54.7±44.8 months.Significant decrease of β2microglobuline pre-dialysis from baseline 26,16 to 20,06 mg/L (p= 0,006) after 3 months and to 17,88smg/L (p= 0.09) after 6 months. xβ2microglobulineRR was 82.45 ±3.20 % and the URR was 79.56±3.51 %, which demonstrates a good removal of medium and small molecules. The Kt/V remained stable (>1,5). Albumin increased from 3.81 g/dL to 3.87 g/dL in e months and to 3.89 g/dL in the 6 months of evaluation. No significant differences in levels of pre-albumin (xbaseline 28 mg/dl). Corporal and BIVA parameters evolution These data shown an improvement of the body composition and water distribution. .Sig. improvements were seen in the appetite scale in the first 6 months (p= 0.09). The total Quality of Life, evaluated in 3 months by SF36, increased from 55,61 to 50,66 (p= 0,05); the physic from 50,28 to 55,92 (p= 0,036); the mental from 55,69 to 60,1 (p= 0,12).Cytokines:we found an increase in neuropeptide Y and IL10 and no significant changes in leptin and adiponectin with slight increase of IL6. CONCLUSIONS: 1-The preliminary results show that MidDilution provides a good removal of small and middle molecules, increases appetite by providing a proper balance of cytokines through stimulation of antiinflamatory ones and neuropeptide Y. 2-It provides an improvement of body composition. Finally MidDilution improves nutritional parameters which leads to a better quality of life, as well as physical and mental status.